THE EDUCATION OF URBAN MANAGERS IN IRAN SINCE 1950S TO 2004 - Mahmud Saeedi REZVANI; Hadi Saeedi REZVANI (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Purpose-This paper tries to describe and evaluate the education and training programs for the municipalities’ staff and the urban mangers in Iran since 1950s, by reviewing the history and changes in these programs. Design/methodology/approach- This article bases its discussion of the urban manager education evolution on the original document about the educational activities at municipalities in Iran. In this way the documentary and criterion methods are used. Findings- The intense activities regarding education of urban managers started with the establishment of the Municipalities Union in 1958. After the Islamic Revolution in 1979 the Development Deputy of the Interior Ministry continued these educational programs after a lapse of two decades. In 2002 the Municipalities Organization was established and these educational programs continued under the new organization. Before the Islamic revolution, these educational programs included 1) Pre-service training and 2) In-service training. The educational programs after the revolution can be classified into three groups: 1) Publication for the purpose of enculturation; 2) longterm courses for educating urban managers; 3) Short-term courses.